A transcendência vivida em sua temporalidade: Sartre e a experiência psicopatológica - Bocca, Marivania Cristina (2019)
From the beginning of his philosophical writings, Jean-Paul Sartre (1905-1980) engaged in a constructive dialogue with psychology and, consequently, with its resulting phenomena, such as psychopathology. This dialogue happened critically. It was, in fact an approximation with a certain distancing. Sartre problematized these disciplines through several epistemological and methodological objections to the theories that were prevailing then. It is from this critical standpoint that the French philosopher covers theoretically, in his extensive and complex work, his cardinal project: to overhaul, beyond existing psychology, a new sense and scope of the experience of psyche- the transcendence temporally experienced by the ego. In order to do this, his journey unfolds into several approaches throughout his work. The first of them demands problematizing the time issue, which will lead to the rearrangement of another status of consciousness. The second one requires the consideration that this consciousness is located, pre-reflexively, as freedom, as an existential project. The third approach constitutes in a clear and critical interaction with Freud and consists in a methodological demand that Sartre calls “Existential Psychoanalysis”. Regarding the aforementioned demand, this is the phenomenological procedure that the French philosopher reorganizes years later, from a dialogue with Marxist traditions, by proposing the method characterised as progressive-regressive, in which the ego temporally experienced is not a stranger to historical conditions. By realigning both of these methodological processes, it is feasible, from a Sartrean perspective, to investigate the viability of a psychological and psychopathological clinical praxis. This thesis, therefore, depicts the clinical case of a female, nosologically diagnosed with Borderline Personality Disorder, who attended psychotherapy. This account shows the complexity that Sartre reported in his works and methods on the dialectical relationship between the subject and the socio-material field. Also, it situates, hermeneutically, how this particular woman communicates her psychophysical sufferings in a reactive and psychopathological way. In the light of these analyses, we aim to understand how phenomena originate socio-historically, being constituted in and by the anthropological and sociological context in which the client was and is inserted.